Analysis of Peruvian scientific production in the context of the COVID-19 pandemic : Analysis of Peruvian scientific production in the context of the COVID-19 pandemic - Becerra-Escobar, Anthony Christian (2021)
Scientific production has not stopped, strengthening research networks and new ways of sharing information aimed at reflecting and solving the problems of the population.